Spreading misandry : the teaching of contempt for men in popular culture - Nathanson, Paul, 1947- (McGill-Queen's University Press, 2001)
Nathanson and Young urge us to rethink prevalent assumptions about men that result in profoundly disturbing stereotypes that foster contempt. Spreading Misandry breaks new ground by discussing misandry in moral terms rather than purely psychological or sociological ones and by criticizing not only ideological feminism but other ideologies on both the left and the right.